Deontic Visual Signs. Between Normative Force and Constitutive Power - Guglielmo Siniscalchi (Rosenberg & Sellier, 2020)
The most of legal theories in the twentieth century have always asserted that rules are product of linguistic utterances and that they have nothing to do with “visual culture”. In this paper I show, on the contrary, that the visual dimension is crucial to understand and found some legal-philosophical discourse. The relationship between images and law is always bi-directional, by the first direction following the way from law to images, and by the second one, vice versa, passing from images into the universe of normative discourse. In these pages I do not explore the second direction; I limit myself to investigate the first way asking two questions relevant for the construction of the legal order: Are there visual signs in the normative language? And, if so, what function do they have?